Nippontonia ashmoreiensis sp. nov., (Crustacea: Decapoda; Pontoniinae) from Ashmore Reef, Western Australia - Bruce, A. J. (Zootaxa, 2014)
An undescribed species of pontoniine shrimp of the genus Nippontonia Bruce & Bauer, N. ashmoriensis sp. nov., collected from a sponge from Ashmore Reef, Western Australia, is described and illustrated.